Identification of novel circulating microRNAs in advanced heart failure by next‐generation sequencing. (2nd May 2021) - Galluzzo, Alessandro; Gallo, Simona; Pardini, Barbara; Birolo, Giovanni; Fariselli, Piero; Boretto, Paolo; Vitacolonna, Annapia; Peraldo‐Neia, Caterina; Spilinga, Martina; Volpe, Alessandra; Celentani, Dario; Pidello, Stefano; et al.
Abstract: Aims: Risk stratification in patients with advanced chronic heart failure (HF) is an unmet need. Circulating microRNA (miRNA) levels have been proposed as diagnostic and prognostic biomarkers in several diseases including HF. The aims of the present study were to characterize HF‐specific miRNA expression profiles and to identify miRNAs with prognostic value in HF patients. Methods and results: We performed a global miRNome analysis using next‐generation sequencing in the plasma of 30 advanced chronic HF patients and of matched healthy controls. A small subset of miRNAs was validated by real‐time PCR ( P < 0.0008). Pearson's correlation analysis was computed between miRNA expression levels and common HF markers. Multivariate prediction models were exploited to evaluate miRNA profiles' prognostic role. Thirty‐two miRNAs were found to be dysregulated between the two groups. Six miRNAs (miR‐210‐3p, miR‐22‐5p, miR‐22‐3p, miR‐21‐3p, miR‐339‐3p, and miR‐125a‐5p) significantly correlated with HF biomarkers, among which N‐terminal prohormone of brain natriuretic peptide. Inside the cohort of advanced HF population, we identified three miRNAs (miR‐125a‐5p, miR‐10b‐5p, and miR‐9‐5p) altered in HF patients experiencing the primary endpoint of cardiac death, heart transplantation, or mechanical circulatory support implantation when compared with those without clinical events. The three miRNAs added substantial prognostic power to Barcelona Bio‐HF score, a multiparametric and validated risk stratification tool for HF (from area under the curve = 0.72 to area under the curve = 0.82). Conclusions: This discovery study has characterized, for the first time, the advanced chronic HF‐specific miRNA expression pattern. We identified a few miRNAs able to improve the prognostic stratification of HF patients based on common clinical and laboratory values. Further studies are needed to validate our results in larger populations.